A seven-color panel including CD34 and TdT could be applied in >97% patients with T cell lymphoblastic leukemia for minimal residual disease detection independent of the initial phenotype. (September 2018) - Wang, Ya-Zhe; Hao, Le; Chang, Yan; Jiang, Qian; Jiang, Hao; Zhang, Le-Ping; He, Ling-Ling; Yuan, Xiao-Ying; Qin, Ya-Zhen; Huang, Xiao-Jun; Liu, Yan-Rong
Highlights: A seven-color panel including CD34 and TdT was built to detect MRD in T-ALL. The panel could be applied to >97% T-ALL patients independent of initial phenotype. Only one MRD false-negative result occurred because of antigen shifts. MRD positive detected by the panel at post-HSCT could effectively predict relapse. Abstract: A seven-color panel was used to detect minimal residual disease (MRD) in T cell acute lymphoblastic leukemia (T-ALL) via flow cytometry (FCM). Its availability and clinical significance were studied in T-ALL patients with newly diagnosed (n = 64), relapsed (n = 48) and morphologically complete remission (n = 103). The following four features were used to identify immature cCD3+ T cells: CD34+, TdT+, but mCD3-/dim+, and CD45dim+. Among these features, either TdT or CD34 expression was the most useful and were found in 93.8% of patients at diagnosis and 86.7% of patients who relapsed. Although some of the immature markers had disappeared in 23 of 59 cases after therapy, only one case presented with a false negative MRD. Of the 74 consecutive patients who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT), MRD-positive patients showed a higher relapse rate, a higher cumulative incidence of relapse at 4 years and a shorter median relapse-free survival than MRD-negative patients at post-HSCT(72.7% vs 17.3%, P = 0.000; 100% vs 19.9%, P < 0.0001; and 16 months vs undefined, P < 0.0001). We demonstrated that this panel could be applied to>97% of T-ALL patients to detect MRD and predict relapse after allo-HSCT even in the absence of the initial immunophenotype.